Analysis of the complete mitochondrial genome sequence of Japanese butterflyfish, Chaetodon nippon (Chaetodontiformes, Chaetodontidae). Issue 3 (4th March 2023) - Patil, Maheshkumar Prakash; Kim, Jong-Oh; Lee, Yu-Jin; Seo, Yong Bae; Kim, Jin-Koo; Kim, Gun-Do
Abstract: Japanese butterflyfish ( Chaetodon nippon ) belong to the family Chaetodontidae and order Chaetodontiformes. It has circular mitochondrial genome of 16, 507 bp in length with 55.4% of A + T content and has 37 genes, including 22 tRNA, 2 rRNA, and 13 protein-coding genes, in addition to a control region. The results of phylogenetic analysis indicated that the C. nippon, C. wiebeli, C. auripes, C. auriga, C. octofasciatus, C. speculum, and C. modestus are closely related to each other. The findings of this study will provide useful genetic information for further phylogenetic and taxonomic classifications of Chaetodontidae.